Work from Home to Prevent the Spread of the Corona Virus - Bachtari Alam Hidayat; Robi Sugara; Suhendri Suhendri; Maya Febriyanti; Ahmad Zikrillah Haikal; Rahmadi Rahmadi; Diki Agustiansyah; Khairul Wazi (Budapest International Research and Critics University, 2022)
Since the first incidence of Covid-19 was discovered, it has developed into a global health hazard, with Indonesia today facing the difficulty of stopping Covid-19 transmission. It is insufficient to prevent the spread of this virus through the use of health protocols. Additionally, the government has implemented a policy of widespread social restriction (PSBB) in red zone districts/cities, which are regions with a high number of confirmed cases. This PSBB strategy is also implemented through the Work from Home policy, which aims to reduce employee visits to the office, hence reducing community mobilization. This study employs a procedure known as literature review, which entails searching for theoretical references that are pertinent to the cases or problems discovered. The purpose of this literature review is to examine work-from-home strategies for preventing the spread of Covid-19. PSBB regulation imposes restrictions on community and office activities. Numerous government agencies have implemented the Work from Home system using the 50% entering the office 50% technique. Additionally, WFH invites teachers to work from home in order to accommodate distance learning policies or to teach online for high school and college students. This guideline was implemented to encourage people to cut back on non-essential activities outside the home. Implementing a work-from-home system, as well as online schools and lectures, is a strategic move by the government to avert a corona virus outbreak that is becoming increasingly prevalent in Indonesia at the moment.